Why have some monetary reforms succeeded and others not? An empirical assessment - Andreas Freytag (Universität zu Köln, Institut für Wirtschaftspolitik (iwp), 2001)
Monetary history is characterised by crisis and reform. The paper is dedicated to an explanation of what makes monetary reforms successful. A cross-sectional econometric analysis is chosen to deal with this problem. It is based on a standard macroeconomic model of commitment and credibility. As the dependent variable, we calculate a post-reform inflation rate. The exogenous variables are the degree of legal commitment and the constraining influence of institutions. The paper allows for the conclusion that monetary commitment, the consideration of institutional constraints and abstinence from the money press are crucial for the success of a monetary reform.
Keywords: E50; 330; Monetary Reforms; Credibility; Commitment; Institutions; Währungsreform; Inflationsbekämpfung; Glaubwürdigkeit; Institutionalismus; Schätzung; Erfolgsfaktor; Welt